Idiopathic pulmonary fibrosis: can cell mediated immunity markers predict clinical outcome?. Issue 7 (July 1990) - Meliconi, R; Lalli, E; Borzì, R M; Sturani, C; Galavotti, V; Gunella, G; Miniero, R; Facchini, A; Gasbarrini, G
Abstract : Most of the cells found in lung parenchyma in patients with idiopathic pulmonary fibrosis are activated T lymphocytes and macrophages. The serum levels of three markers of cell mediated immunity were measured in 20 patients with idiopathic pulmonary fibrosis, in 20 normal subjects and in 12 patients with sarcoidosis to evaluate their clinical and prognostic significance in idiopathic pulmonary fibrosis. The three markers were: soluble CD8 (from activated suppressor-cytotoxic lymphocytes), soluble interleukin (IL)-2 receptors (from activated T cells and macrophages), and neopterin (from activated macrophages). Patients with idiopathic pulmonary fibrosis had higher levels of all three markers than the control subjects. Soluble IL-2 receptor and neopterin tended to be lower (though not significantly) in patients with idiopathic pulmonary fibrosis than in those with sarcoidosis, whereas soluble CD8 was similar in the two groups of patients. No correlation was found between soluble IL-2 receptors or soluble CD8 and the clinical, radiological, and physiological measures of disease activity or with clinical outcome (after a mean follow up of 23 months). Tumour necrosis factor levels were also determined. Only 30% of patients with idiopathic pulmonary fibrosis or sarcoidosis had detectable circulating tumour necrosis factor; these patients had a lower percentage of bronchoalveolar lavage fluid neutrophils in their lavage fluid. Tumour necrosis factor levels did not correlate with clinical measures of severity or outcome. Thus our data support the hypothesis that cell mediated alveolitis occurs in idiopathic pulmonary fibrosis. They do not, however, provide evidence to support the use of these markers of cell mediated immunity to monitor the clinical course in these patients.